Mandibular involvement as a first sign in Multiple Myeloma: a case report - Raut, Mugdha; Bansal, Shivani; Sharma, Ankit; Desai, Rajiv (Brazilian Dental Science, 2018)
Objective: To report a case of Multiple myeloma (MM) in mandible with paraesthesia. Material and Methods: The present case report highlights the occurrence of a swelling in the left posterior mandibular region in a 70-year old female patient and draws attention to the first clinical sign of a widespread systemic disease manifesting in the head and neck region. Results: The initial presumptive diagnosis was invalidated by the histopathological examination and other diagnostic tests that revealed the features characteristic for MM. Conclusion: Being a rare disease, MM should be kept on forefront of differential diagnosis for jaw lesions in a geriatric patient with paraesthesia.Keywords:  Multiple myeloma; Mandible; Paraesthesia.